2016
DOI: 10.1007/s00441-016-2436-4
|View full text |Cite
|
Sign up to set email alerts
|

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia

Abstract: Increased circulating syncytiotrophoblast microparticles (STBMs) are often associated with preeclampsia (PE) but the molecular mechanisms regulating STBM shedding remain elusive. Experimental evidence has shown that actin plays a key role in STBM shedding and that Rho/ROCK is important in regulating actin rearrangement. To investigate the role of RhoB/ROCK-regulated actin arrangement in STBM shedding in PE, chorionic villous explants were prepared from placenta of patients with normotensive or PE pregnancies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…SDEVs are alternatively called placental syncytiotrophoblast microvillous membrane (Cockell et al, 1997; Aly et al, 2004), syncytiotrophoblast microparticles (Han et al, 2016) and placental-derived microvesicles (Holder et al, 2012). Similar to EVs of other cells, SDEVs are highly heterogeneous in their morphology, carried cargos, biological properties, and activities toward target cells.…”
Section: Structure and Function Of Sdevsmentioning
confidence: 99%
See 1 more Smart Citation
“…SDEVs are alternatively called placental syncytiotrophoblast microvillous membrane (Cockell et al, 1997; Aly et al, 2004), syncytiotrophoblast microparticles (Han et al, 2016) and placental-derived microvesicles (Holder et al, 2012). Similar to EVs of other cells, SDEVs are highly heterogeneous in their morphology, carried cargos, biological properties, and activities toward target cells.…”
Section: Structure and Function Of Sdevsmentioning
confidence: 99%
“…Together, these pathological activities induced by SDEVs are significantly exaggerated in PE to restrict fetal growth and result in recurrent miscarriage (Lok et al, 2011; Baig et al, 2013). Han et al (2016) recently reported that the RhoB/ROCK-regulated actin arrangement promotes the shedding of SDEVs from syncytiotrophoblasts in PE patients, indicating that regulating RhoB/ROCK signaling may be a new therapeutic strategy for patients with PE.…”
Section: Structure and Function Of Sdevsmentioning
confidence: 99%
“…38 Upregulation of RhoB/ROCK, regulators of actin rearrangement, increased STBEV release in vitro; moreover RhoB/ROCK knockdown reduced STBEV release in a hypoxic model of PE. 39 Vitamin D supplementation has been shown to reduce ROCK1 activation in trophoblast cultures, which could contribute to the clinically preventative effect of vitamin D supplementation in PE. 40 Substantially more work is needed to confirm this theory.…”
Section: Stbev Release In Pementioning
confidence: 99%
“…The ROCK1 activity was evaluated by immunoprecipitating ROCK1 and then performing an in vitro kinase activity assay (Mong and Wang, 2009;Han et al, 2016). Cells were lysed using a lysis buffer and then incubated for 1 h at 4 • C with 2 µg of isotype control IgG, rabbit anti-ROCK1.…”
Section: Evaluation Of the Activity Of Rock1mentioning
confidence: 99%